Բանկային համակարգի կայունության բարելավման ուղիները ՀՀ-ում - Ռաֆիկ Հարությունյան (ՀՀ ԳԱԱ հրատ.)
Банковская система РА не в полной мере соответствует целям устойчивого развития экономики. Это негативно отражается на долгосрочной устойчивости экономики. В данной статье рассматриваются пути укрепления стабильности банковской системы Армении, которые одновременно будут спососбствовать устойчивому развитию экономики страны. The banking system of Armenia is inadequate for the sustainable development of the economy, which ,after all, adversely affects its long-term sustainability. This article examines the ways of strengthening the stability of the Armenian banking system, which will also contribute to the sustainable development of the Armenian economy.
Keywords: Social Sciences; Economic Theory; Banking